IMPLEMENTASI CLOSED CIRCUIT TELEVISION UNTUK PENINGKATAN KEAMANAN PERUMAHAN GRIYA SALAK MADIUN - Nisaul Hafidhoh; Susilo Veri Yulianto; Muhammad Syaeful Fajar; Gus Nanang Syaifuddiin; Hendrik Kusbandono; Bayu Prasetiyo Utomo; Zidni Zidan Mahestra Setyawan; Nabila Carrissa Dewi (Universitas Muhammadiyah Ponorogo, 2026)
Neighborhood security is a key factor in creating a good quality of life in residential areas. Cases of theft, vandalism, and even inconvenience caused by unknown visitors frequently pose a threat to the community. This situation demands a more effective and responsive surveillance system in residential areas. Traditional surveillance methods, such as patrols or manual security, often experience various limitations, both in terms of human resources, operational time, and coverage area. This activity aims to improve neighborhood security through the implementation of a Closed Circuit Television (CCTV) system in the Griya Salak Housing Complex, Madiun City. The implementation method includes a needs analysis, CCTV network design with a hybrid topology, device installation including IP cameras and Network Video Recorders (NVRs), and system usage training for residents. The results of the activity show an increase in surveillance effectiveness and a sense of security for residents, as well as increased community participation in the management of the technology-based security system. The implementation of this CCTV system is expected to become a model for digital security that can be replicated in other residential areas.